2016
DOI: 10.1007/s10554-016-1019-5
|View full text |Cite
|
Sign up to set email alerts
|

High-risk carotid plaques identified by CT-angiogram can predict acute myocardial infarction

Abstract: Purpose Prior studies identified the incremental value of non-invasive imaging by CT-angiogram (CTA) to detect high-risk coronary atherosclerotic plaques. Due to their superficial locations, larger calibers and motion-free imaging, the carotid arteries provide the best anatomic access for the non-invasive characterization of atherosclerotic plaques. We aim to assess the ability of predicting obstructive coronary artery disease (CAD) or acute myocardial infarction (MI) based on high-risk carotid plaque features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The degree of luminal stenosis, plaque thickness, surface ulceration and remodeling index (RI = the maximum wall thickness at the most stenotic site/the wall thickness at the nearby disease-free site) were calculated or identified. Positive soft plaque was defined as maximum soft plaque thickness >2 mm [ 25 ], and a positive remodeling index was reported as RI ≥ 1.1 [ 26 ]. The mean plaque Hounsfield unit (HU) was defined as the average HU in the region between the lumen and outer wall contour across the whole plaque volume [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The degree of luminal stenosis, plaque thickness, surface ulceration and remodeling index (RI = the maximum wall thickness at the most stenotic site/the wall thickness at the nearby disease-free site) were calculated or identified. Positive soft plaque was defined as maximum soft plaque thickness >2 mm [ 25 ], and a positive remodeling index was reported as RI ≥ 1.1 [ 26 ]. The mean plaque Hounsfield unit (HU) was defined as the average HU in the region between the lumen and outer wall contour across the whole plaque volume [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…CTA can establish plaque stenosis rates as accurately as conventional digital substraction angiography (DSA). CTA is generally preferred over DSA, because CTA is noninvasive and can depict vascular wall pathologies, plaque morphology, and extravascular tissues in addition to the vascular lumen (14,15). CTA scans provide vital information to the clinician, as the rate of carotid stenosis and the nature of the atherothrombotic plaque play an important role in determining the course of treatment (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the presence of iodine in the plaque is mainly due to neovascularization, 23,24 and it could be associated with an increased, systemic atherosclerotic activity as demonstrated in a recent published study that demonstrated the association between carotid plaque features and increased risk of myocardial infarction. 25 Following this hypothesis, the presence of atherosclerotic disease, with plaques that show contrast (detected with the keV variation), could be considered as a surrogate marker of LA.…”
Section: Discussionmentioning
confidence: 99%